Audit Fees: The Role of Board of Commissioners Size, Audit Committee Size, and Firm Size - Najma Alaika Selma; Anitaria Siregar (Magister Akuntansi FB-UK.Maranatha, 2026)
Audit fees represent an essential component of audit services as they reflect audit effort, complexity, and the level of risk involved in the audit process. This study aims to analys the effect of firm size, audit committee size, and board of commissioners size on audit fees of manufacture companies listed on the BEI with the period 2022–2024. This research usess a quantitative approach and the data were analyzed using multiple linear regression with IBM SPSS version 26. The results indicate that board of commissioners size has a significant effect on audit fees, implying that a larger board increases monitoring requirements, which in turn leads to higher audit effort and fees. Furthermore, audit committee size is found to significantly affect audit fees, as a larger audit committee demands more comprehensive audit procedures to ensure higher reporting quality. Firm size also has a significant positive effect on audit fees, suggesting that larger firms tend to have more complex operations and higher audit risk. In addition, the results show that all independent variables jointly influence audit fees. These findings confirm that corporate governance mechanisms and firm characteristics play an important role in determining levels.